DNA barcoding cannot discriminate between Sardinella tawilis and S. hualiensis (Clupeiformes: Clupeidae). Issue 2 (3rd July 2019) - Chan, Alison Faye O.; Luczon, Adrian U.; Fontanilla, Ian Kendrich C.; Ong, Perry S.; Santos, Mudjekeewis D.; Willette, Demian A.; Quilang, Jonas P.
Abstract: Sardinella tawilis, the only known freshwater sardinella in the world, is endemic to Taal Lake, Philippines. Previous studies found the Taiwan sardinella, S. hualiensis, to be morphologically very similar to S. tawilis and identified it as the marine sister species of S. tawilis . In this study, DNA barcoding using the mitochondrial cytochrome c oxidase I (COI) gene was carried out to analyze species demarcation in the Sardinella genus, focusing primarily on the relationship between S. tawilis and S. hualiensis . The neighbour-joining (NJ) tree that was constructed using Kimura 2-parameter (K2P) model showed a single clade for the two species with 100% bootstrap support. K2P interspecific genetic divergence ranged from 0% to 0.522%, which is clearly below the suggested 3–3.5% cutoff for species discrimination. Recombination activating gene 1 (RAG1), mitochondrial control region (CR), cytochrome b, 16S rRNA, and S7 markers were used to further validate the results. Sardinella tawilis and S. hualiensis clustered together with a bootstrap support of 99–100% in each of the NJ trees. Low interspecific genetic distances between S. tawilis and S. hualiensis for all the markers except CR could be attributed to incipient allopatric speciation.